A risk ranking strategy for network level bridge management - Onoufriou, Toula; Sathananthan, Saenthan; Rafiq, Meena Imran (My University, 2010)
This paper presents the development of a qualitative risk ranking strategy for characterising a network of bridges into groups with similar risk levels, which can form the basis for developing a risk based inspection regime over a bridge network. The factors affecting risk are identified and rationally combined to present various attributes of bridges. A qualitative scoring system is then introduced that uses the attributes to rank bridges in terms of their relative risk. Sensitivity analysis is performed to quantify the effect of relative weights of the attributes on the risk scores. The methodology is demonstrated through its application on the UK's Network Rail bridge stock and a random sample of bridges is ranked according to the proposed method. One of the factors used to evaluate the risk scores is comparable with the bridge condition index. A reasonable agreement between them is observed within the sample bridges. The proposed method will be beneficial to bridge owners in identifying the bridges according to their risk levels in a simple and systematic manner. Inspections and interventions can be planned based on this risk ranking strategy to maintain a consistent risk level across the network.
Keywords: Risk assessment; Risk analysis